The Influence of Tug Tugboat Services and Vessel Document Readiness On The Productivity of The MT Akra 102 Vessel Agency Agencyd By PT Transuta Lintas Samudera, Merak Branch - Aprilesa Sahata Marel Sinaga; April Gunawan Malau; Supardi Supardi; Brenhard Mangatur Tampubolon; Roy Kasiono (Dinasti Publisher, 2024)
This study aims to determine the effect of tugboat services and ship document readiness on the productivity of the MT Akra 102 Ship Agency, which is represented by PT Transuta Lintas Samudera, Merak Branch. PT. Transuta Lintas Samudera is a shipping company engaged in shipping agency services for domestic and foreign ships in the Merak Port area. There are several problems with delays in the berthing of foreign ships that occurred at the Port of Banten. An example is the ship MT. AKRA 102 which is routinely agented every time it comes to the Merak Port area. PT Transuta Lintas Samudera, Merak Branch is one of the companies engaged in ship agency services. There is a phenomenon of non-fulfillment of MT ship productivity targets. AKRA 102 expected by the company with what happened in the field. Especially in June, August, October and December in 2021 and in May and June in 2022 which was caused by delays in pilot tugboat services and readiness of ship documents. This can affect consumer confidence in agency companies which can lead to reduced company income. The approach method used in this study uses a quantitative approach. The target population in this study were ship agents, ship owners, jetty masters and company employees with a sample of 45 respondents. The sampling technique in this study uses saturated samples, research uses quantitative data types. Quantitative data obtained from this study is data from the results of respondents' answers presented in the form of a Likert scale. Data collection techniques by distributing questionnaires or questionnaires directly to respondents. The data statistical method used is descriptive statistics and SPSS version 25.0.